INDICATION OF GOLD AND SILVER OCCURRENCE AT SAMPIT BAY, KOTA WARINGIN TIMUR DISTRICT, CENTRAL KALIMANTAN PROVINCE - I Wayan Lugra; Udaya Kamiludin (BULLETIN OF THE MARINE GEOLOGY, 2013)
The study area is fluviatile deposit which consists of yellow to light gray loose sand, iron oxide, and kaoline spreading from the land shallowing to sea direction. Concentration grade for determining of gold and silver content used a total analysis of the hot mixture HF-HNO3-HClO4 with measurements "Atomic Absorption Spectrofotometry".(AAS). Highest concentration of gold and silver found at sample GCTS-31 that gold 0.096 ppm and silver 2.284 ppm, in muddy sand type sediment, at 3.1 meters depth and arround 1,250 meter length from coast line. While the lowest concentration of the gold was 0.025 ppm found at sample GBTS 14 in very fine sand type sediment located at 1.07 meter depth and approximately 320 meters length from coast line. The lowest concentration of the silver was founded at sample GBTS 25 that is 0.860 ppm in sandy mud sediment type located at 2.49 meters depth and approximately 3,000 meters length from the coast line. The gold placer is may derived from weathering of Pambuang Formation which spreads in the west and north of Sampit Bay, and transported by Mentaya River and longshore current system. Key word : sediment samples, laboratory analyses, gold, silver and Sampit Bay. Daerah penelitian merupakan endapan fluviatil terdiri dari pasir lepas berwarna kuning muda sampai abu-abu pucat, oksida besi, dan kaolin yang memiliki sebaran makin mendangkal ke arah laut. Kadar konsentrasi untuk menentukan kandungan emas dan perak menggunakan analisis total campuran HF-HNO3-HClO4 dengan metoda AAS. Analisa besar butir digunakan untuk memisahkan sedimen fraksi kasar sedangkan analisa pipet dilakukan terhadap sediment fraksi halus. Kadar emas dan perak tertinggi terdapat pada contoh GCTS -31, yaitu emas 0,096 ppm dan perak 2,284 ppm, pada jenis sedimen lumpur pasiran, di kedalaman 3,1 meter dan sekitar 1.250 meter dari garis pantai. Sedangkan kadar emas terendah yaitu 0,025 ppm terdapat pada contoh GBTS 14 pada jenis sedimen pasir sangat halus di kedalaman 1,07 meter dan sekitar 320 meter dari garis pantai. Kadar perak terendah dijumpai pada contoh GBTS 25 yaitu 0,860 ppm dengan jenis sedimen pasir lumpuran pada kedalaman 2,49 meter dan sekitar 3.000 meter dari garis pantai. Sumber emas plaser diperkirakan dari lapukan Formasi Pembuang yang memiliki sebaran cukup luas di sebelah barat dan utara Teluk Sampit dan ditransportasi oleh Sungai Mentaya dengan anak-anak sungainya, serta sistem arus memanjang pantai. Kata kunci : contoh sedimen, analisis laboratorium, emas, perak dan Perairan Teluk Sampit.